Pengaruh Kinerja Keuangan Terhadap Nilai Perusahaan Dimoderasi Good Corporate Governance - Saragih, Afni Eliana; Forever, Febiwenesya (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2024)
Capital market statistics for 2023 show that the number of investors has increased sharply, interpreting that company performance is increasingly being highlighted by the public. This research aims to test whether return on assets, return on equity, net profit margin influence company value, moderated by good corporate governance. Using panel data, there are 42 banking companies listed on the Indonesian Stock Exchange in the last 5 years (2018-2022). The influence of the independent variable on the dependent variable and moderating variable was tested using linear regression analysis for panel data. The research results found that return on equity had a significant effect on company value, while return on assets and net profit margin did not have a significant effect on company value. This research also shows that good corporate governance can strengthen the influence of net profit margin on company value. Meanwhile, the existence of good corporate governance as a moderating influence of return on assets and net profit margin on company value does not show significant results.